Prevalence of needlestick injuries and factors associated with their occurrence among health care workers at a private hospital in northern Namibia - Enos Moyo; Tafadzwa Dzinamarira; Malizgani Mhango; Shingairai Feresu; Perseverance Moyo (Human Factors in Healthcare, 2022)
Background: Although needle stick injuries (NSIs) are a very common preventable occupational hazard among healthcare workers (HCWs), their prevalence remains high. The study aimed to assess the prevalence of NSIs, and factors associated with NSIs among HCWs at a private hospital in northern Namibia. The HCWs included enrolled nurses, registered nurses, and doctors. Methods: An analytic cross-sectional study design was used for the study. 400 respondents were selected using a proportional stratified random sampling method. A self-administered questionnaire designed for the study was used for data collection. Statistical analysis employed Chi-square tests and logistic regression. Results: The 12 months prevalence rate of NSIs among HCWs was 37.5%, 95% CI (32.8% – 42.2%), while the career prevalence was 55.3%, 95% CI (50.4% – 60.2%). Most NSIs (30.3%) occurred in theatre, 40.3% were caused by syringe needles, 70.5% occurred on fingers, and 74.7% were of a prick nature. Chi-square tests showed an association between profession and NSIs and between work experience and NSIs (p<0.01). Nurses were more likely to experience NSIs in the past 12 months compared to doctors, AOR = 4.31, 95% CI (1.50 – 12.38). Respondents with 2-5 years of work experience were less likely to experience NSIs in the past 12 months compared to those with less than two years of work experience, AOR = 0.36, 95% CI (0.21 – 0.62). Conclusion: The findings of the study accentuate the need for hospital authorities to strengthen employees’ training on handling sharp instruments and support the use of instruments with safety features.